Toxic Positivity and Mental Health Help-Seeking Intentions and Attitudes among Filipino High School Students - Garcia, Roselle; Gonzalo, Nerisa T. (Journal of Educational, Health and Community Psychology, 2025)
This study explores the emerging trend of toxic positivity among high school students, a topic with limited prior research. It examines behavioral and attitudinal patterns related to toxic positivity, help-seeking intentions, and attitudes, differentiated by gender and grade level. The participants included 263 public high school students in Baguio City, Philippines. Data were collected using the MHSIS, ATSPPH-SF, and TPT. Findings demonstrated excellent reliability for the MHSIS scale (α = 0.906), as well as acceptable to moderate reliability levels for the ATSPPH (α = 0.616) and TPT (α = 0.669). Results further indicate that female students exhibit slightly higher levels of toxic positivity than male students. Students in grades 7 and 8 are more inclined to seek professional assistance. Specifically, grade 8 students consistently demonstrated a stronger intention to seek help than grade 9 students. Additionally, a negative correlation was identified between toxic positivity and help-seeking attitudes: higher toxic positivity levels correlate with reduced help-seeking intentions, and vice versa. The study concludes with recommendations for future research and suggests the development of a School-Based Mental Health and Wellness Program.